Ruptured splenic artery pseudoaneurysm: is surgery always required? - Bakhshi, Girish D.; Patil, Kanishk N.; Sholapur, Sachin S.; Gutte, Avinash; Sable, Chandrakant; Patel, Owais; Barfiwala, Parth D. (International Surgery Journal, 2021)
Splenic artery aneurysms are extremely rare, and pseudoaneurysms are even rarer. More often than not, the aetiology is acute or chronic pancreatitis, although blunt trauma to abdomen and previous endovascular procedure (iatrogenic) are also known causes. The condition can have a wide spectrum of clinical presentations ranging from incidental finding to severe uncompensated circulatory shock. Splenic artery pseudoaneurysm (SAP) is frequently misdiagnosed as a pseudocyst pancreas with haemorrhage in it, as was the case with one of the present patients. In this case series, we discuss two patients of SAP. A young 33-year-old male patient, known case of pancreatitis, who presented with severe hypotension and ultrasonography (USG) suggestive of hemoperitoneum and pseudocyst pancreas with hematoma. The second patient was a 42-year-old male who presented with acute onset upper abdominal pain, vomiting, abdominal distension and giddiness. Both these patients were resuscitated by giving fluids and blood transfusions. Their diagnosis of SAP was confirmed on computed tomography (CT) of abdomen. Both these patients underwent endovascular coiling of SAP. Present report highlights the role of endovascular intervention in managing a bleeding SAP as long as emergency surgical team are kept on stand-by.